The Kasultanan and Kadipaten Land (SG/PAG) After the YSL Enactment: Strengthening of The Patrimonial Culture and Counter Agrarian Reform - Angger Budiadji; Hari Purwadi; Widodo Tresno Novianto (Journal of Social Research, 2023)
The purpose of this article is to identify some issues arising from the revival of the SG/PAG after the enactment of the Yogyakarta Speciality Law (YSL). This article seeks to identify three issues arising from re-emerging the SG/PAG after the enactment of the YSL. First, the strengthening of patrimonial culture in Yogyakarta. Second, the SG/PAG impact on the common people in Yogyakarta. We will answer two research questions: (1) How relation between SG/PAG revival and the strengthening of Patrimonial Culture and (2) What is the impact of the revival of SG on the prosperity of the People? The results of the research. The results showed that the patrimonial culture in Yogyakarta strengthened after the YSL was enacted and also land grabbing informal land and village land, on the other hand, patrimonialism cloaked as a 'Speciality of Yogyakarta' actually weakened state control over land in Yogyakarta.